The black-legged kittiwake preen gland—an overlooked organ for depuration of fat-soluble contaminants? - Solheim, Silje Aakre; Sagerup, Kjetil; Huber, Sandra; Byrkjedal, Ingvar; Gabrielsen, Geir Wing (Polar Research, 2016)
Most birds preen their feathers with an oily excrete from the uropygial (preen) gland. This oily excrete contains persistent organic pollutants (POPs), which make the preen gland a potential route of depuration of POPs in birds. Black-legged kittiwakes (Rissa tridactyla) were studied during two periods of high energy demand: incubation and chick-rearing. A rather high concentration of POPs in preen gland tissue indicates that the preen gland secrete is an excretory pathway for POPs in kittiwakes. The similarity in the POP profile detected in this study of liver, preen gland and feathers suggests that POPs found in the feathers are excreted through the preen gland. The finding also indicates that excretion of POPs through the preen gland is compound unspecific. This qualitative study should be followed up by a new quantitative study to determine the importance of excretion of POPs through the preen gland. publishedVersion